2021
DOI: 10.2147/vhrm.s299272
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Self-Reported Cardiovascular Diseases Among a Nationally Representative Population-Based Sample of Adults in Ecuador in 2018

Abstract: Background This study aimed to determine the prevalence and correlates of self-reported cardiovascular diseases (SRCVDs) among adults in Ecuador. Methods National cross-sectional survey data of 4638 persons aged 18–69 years in Ecuador were analysed. Research data were collected with an interview-administered questionnaire, physical and biochemical measurements. Results The prevalence of SRCVDs was 8.7%, 8.5% among men and 8.9% among women. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Furthermore, the study found associations between poor mental health (neurological or psychiatric problems, sleep symptoms, poor mental health and in unadjusted analysis probable depression) and SRA, which is consistent with previous results ( 5 , 10 , 18 21 , 26 – 28 ). The association between sleep problems and arthritis may be related to pain at night ( 19 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Furthermore, the study found associations between poor mental health (neurological or psychiatric problems, sleep symptoms, poor mental health and in unadjusted analysis probable depression) and SRA, which is consistent with previous results ( 5 , 10 , 18 21 , 26 – 28 ). The association between sleep problems and arthritis may be related to pain at night ( 19 ).…”
Section: Discussionsupporting
confidence: 92%
“…The study found that the cross-sectional prevalence of SRA (4.0%) was lower than in previous studies among middle-aged and older adults in India (14.7%) ( 6 ), in six lower resourced countries (19.9% among women and 14.1% among men) ( 4 ), in China (31.4%) ( 7 ), in South Africa (24.7%) ( 5 ), and in Mexico ( 18 ). The lower prevalence of SRA in Thailand may be attributed to a lower rate of some risk factors, such as obesity, compared to other middle-income countries ( 7 ).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations